Penerapan Kompetensi Pedagogik Tutor dalam Meningkatkan Partisipasi Belajar Peserta Didik Program Paket C Kelas Reguler di SPNF SKB Kabupaten Mojokerto - Nonik Dwi Ayu Siswati; Sjafiatul Mardliyah (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2023)
This study aims to examine the application of tutors' pedagogic competence in increasing learning participation of regular class C package C students at SPNF SKB Mojokerto Regency. This research uses a type of descriptive research with a qualitative approach. The results showed that the pedagogical competence of tutors in increasing the learning participation of regular class C package learners applied by all tutors is educational and dialogical learning, it is proven that learners dare to adapt. Tutors have an understanding of students to determine how to teach to be more precise and minimize errors. 5 tutors organize remedial to provide opportunities for learners to develop their potential. Student learning participation includes asking questions about material that is not understood, answering questions given by the tutor, expressing opinions or refutations about the amount of material delivered by the tutor, doing structured assignments for 11 subjects in class well and making material notes for 11 subjects.